Disruptor or accelerator: COVID-19's impact on the Australian sport industry - Karg, A.; Robertson, J.; Dinsdale, S. (SportNXT, 2021)
A year after COVID-19 reached Australia`s shores, the impact has been wide ranging. This report provides an analysis of the pandemics impact on the Australian sport industry, and investigates the responses from, and lessons learnt by, senior sport executives in a year of substantive disruption. This report collates experiences and perspectives based on roundtables and interviews conducted with senior sport executives in October-November 2020, six months after the disruption caused by the COVID-19 shutdowns.Mirrored by the longitudinal nature of our research, leaders discussed impacts that ranged from immediate health and safety demands, to remodelling operational and financial sustainability in the mid- to long-term. In this light, we recognise that our research represents a starting point to assess the lessons learnt from the most disruptive local and global crisis in half a century. Nonetheless we hope this initial work serves as a moment of reflection for the Australian sport industry as it moves through and past the pandemic. Finally, in developing and authoring this report, we acknowledge and thank the many CEOs and senior leaders who spent time with us and openly shared their invaluable experiences from leading Australian sport through COVID-1. (Adam Karg, Swinburne University of Technology Jonathan Robertson, Deakin University Scott Dinsdale, FutureNext / SportNXT)